Germany : Financial Sector Assessment Program Technical Note-Regulation And Supervision Of Less Significant Institutions. (IMF Staff Country Reports; Country Report, 2022)
The Financial Sector Assessment Program (FSAP) conducted a focused review that primarily assessed banking regulation and supervision of Germany's less significant institutions (LSIs).1 Germany accounts for 1,324 of about 2,400 total LSIs in the Euro Area (representing 40 percent of Germany's banking sector assets and approximately 55 per cent of total Euro Area LSI assets). As Germany is part of the Euro Area, the regulation and supervision of banks takes place within the European Central Bank's (ECB) Single Supervisory Mechanism (SSM). The Federal Financial Supervisory Authority (BaFin) and the Deutsche Bundesbank (BBk) are responsible, under the oversight of the ECB, for the supervision of LSIs.